The Effect of Problem-Based Learning on Students’ Cognitive Ability in Vocational Fuel System Learning - Dance Putra Y. Tanesab; Damianus Manesi; Dzakwan Murtadlo Mukti; Fahrizal Fahrizal (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to examine the effect of the problem-based learning approach on improving students’ cognitive ability in vocational fuel system learning. Methods – A quantitative method with a one-group pretest posttest design was employed. The participants consisted of 37 eleventh-grade vocational students. Data was collected through cognitive tests, classroom observation, and documentation. Data analysis included normality testing, a one-sample t-test, and N-Gain analysis. Findings – The results showed an increase in the mean score from 61.76 (pretest) to 84.32 (posttest). The posttest mean exceeded the minimum mastery criterion (75). Statistical testing indicated a significant result (p < 0.05). The N-Gain score of 0.60 was categorized as moderate, indicating a meaningful improvement in students’ cognitive ability.Research Implications – The findings indicate that the problem-based learning approach contributes to improving students’ cognitive performance in vocational learning contexts, particularly in fuel system material. This study is limited to using a one-group pretest-posttest design and a single-class sample, which restricts causal inference and generalizability. Future studies are recommended to apply control group designs, larger samples, and broader contexts.